Facile Synthesis of Single Crystal Vanadium Disulfide Nanosheets by Chemical Vapor Deposition for Efficient Hydrogen Evolution Reaction. (21st August 2015) - Yuan, Jiangtan; Wu, Jingjie; Hardy, Will J.; Loya, Philip; Lou, Minhan; Yang, Yingchao; Najmaei, Sina; Jiang, Menglei; Qin, Fan; Keyshar, Kunttal; Ji, Heng; Gao, Weilu; et al.
<x xml:space="preserve">Abstract</x> A facile chemical vapor deposition method to prepare single‐crystalline VS2 nanosheets for the hydrogen evolution reaction is reported. The electrocatalytic hydrogen evolution reaction (HER) activities of VS2 show an extremely low overpotential of −68 mV at 10 mA cm−2, small Tafel slopes of ≈34 mV decade−1, as well as high stability, demonstrating its potential as a candidate non‐noble‐metal catalyst for the HER.